English stative verbs ‘hope’ and ‘love’ and the progressive aspect: in examples from COCA - Chłopek, Dorota (Slavia Centralis, 2021)
The objective of the present paper is to introduce non-native speakers of English to COCA examples of usage of not very popular constructions, such as ‘I am hoping’ and ‘I am loving’, containing stative verbs in the progressive aspect. Stative verbs typically do not exhibit the progressive aspect. Nonetheless, as instances of COCA concordances demonstrate, there are ‘special’ situations in which native speakers of English, in this case American English, may communicate using the said constructions. Lexical and grammatical aspects plus speaking habits produce constructions which are sanctioned only in specific circumstances. COCA demonstrates numerous situations in which different sources of authentic English display the said stative verbs in the progressive aspect. Hence, the present article signals the said issues.
Keywords: English; lexical aspect; progressive aspect; stative verbs; corpus; concordance; special usage